A wavelike buffer for introducing samples into autonomous capillary microfluidic devices. (23rd November 2016) - Li, Jingmin; Liang, Chao; Wang, Shuai; Guo, Lihua; Liu, Ziyang; Liu, Chong
Abstract: The microfluidic technique has gained attention due to its advantages in providing a rapid diagnostic result for on-site diagnosis and treatment. To obtain a quantitative and reproducible diagnostic result the fluid flow in the microfluidic device must be steady. However, a non-specific flow will always form due to the disturbances introduced during the sample injecting process. Here, a wavelike sample introduction buffer is presented. The buffer can change the longitudinal flow of the injected sample to a transverse flow, which will consume the kinetic energy and eliminate disturbances. By using the buffer, fluid flow within a microfluidic device can become steady. The effects of the buffer parameters on buffering performance have been studied. Results show that the buffering performance increases as the waved peak height and peak number decrease. This buffer has a simple structure. It requires no external power supplies or complicated fabrication process. It will be helpful in improving the diagnostic accuracy of microfluidic devices.